Atomic Energy is Here to Stay: How We Use it is the Business of Every Citizen - United States. Office of Education (Atomic energy here to stay, 1949)
Illustration of an atom radiating out to four sectors of the economy: Industry, Agriculture, Medicine, and Power. This back cover of the magazine is meant to cement the idea that atomic energy is the future of business. This is a magazine supplement meant to inform the educational leaders of the United States about the need for schools to address atomic energy with their students. It frames atomic energy as the future of the economy and challenges schools to train the students for this future economy.
Keywords: Nuclear energy--Economic aspects; Technology and state; Nuclear energy; Nuclear energy--Research; Nuclear energy--Social aspects; Education